Native sources of Japanese industralization, 1750-1920 - Smith, Thomas C. (University of California, 1988)
Premodern economic growth: Japan and the West --- The land tax in the Tokugawa period --- Farm family by - employments in preindustrial Japan --- Peasant families and population control in eighteenth - century Japan --- Japan's aristoractic revolution --- The discontented...